2010
DOI: 10.1039/b920033a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative DFT study of structure and magnetism of TMnOm (TM = Sc–Mn, n = 1–2, m = 1–6) Clusters

Abstract: A systematic theoretical study of the structural and magnetic properties of small transition metal oxide clusters TM(n)O(m) (TM = Sc, Ti, V, Cr and Mn; n = 1, 2; m = 1-6) has been carried out by using an ab initio density functional theory approach. The O atoms are partly molecularly adsorbed in O-rich and few-valence electron TM oxide clusters like ScO(3), TiO(3), Sc(2)O(4-6), Ti(2)O(5-6), and V(2)O(6). The binding energy increases monotonously with increasing O atoms and decreases with the appearance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 62 publications
4
30
0
2
Order By: Relevance
“…The most stable structure of Ni 2 O 4 is a planar configuration in an antiferromagnetic state and two terminal O atoms forming a peroxide unit, different from the cases of Fe 2 O 4 and Co 2 O 4 . The energetically preferred magnetic states are triplet and singlet, respectively, for Ni 2 O 5 and Ni 2 O 6 , and the terminal O atoms also prefer to form peroxide units.From above discussions, together with our earlier results of TM n O m (TM = Sc, Ti, V, Cr and Mn, n = 1 and 2, m = 1-6),8 we found that transition metal oxide clusters prefer tridimensional architectures from Sc to Fe, while Co Delivered by Ingenta to: McMaster University IP: 91.200.81.113 On: Fri, 10 Jun 2016 12:37:48 Copyright: American Scientific Publishers Wang et al Ab Initio Study of Structure and Magnetism of Late Transition Metal Oxide TM n O m Clusters and Ni oxide clusters tend to adopt planar conformations and the terminal O atoms are inclined to form peroxide unit with increasing concentration of O atom. The specific physical reason is still unclear to us.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The most stable structure of Ni 2 O 4 is a planar configuration in an antiferromagnetic state and two terminal O atoms forming a peroxide unit, different from the cases of Fe 2 O 4 and Co 2 O 4 . The energetically preferred magnetic states are triplet and singlet, respectively, for Ni 2 O 5 and Ni 2 O 6 , and the terminal O atoms also prefer to form peroxide units.From above discussions, together with our earlier results of TM n O m (TM = Sc, Ti, V, Cr and Mn, n = 1 and 2, m = 1-6),8 we found that transition metal oxide clusters prefer tridimensional architectures from Sc to Fe, while Co Delivered by Ingenta to: McMaster University IP: 91.200.81.113 On: Fri, 10 Jun 2016 12:37:48 Copyright: American Scientific Publishers Wang et al Ab Initio Study of Structure and Magnetism of Late Transition Metal Oxide TM n O m Clusters and Ni oxide clusters tend to adopt planar conformations and the terminal O atoms are inclined to form peroxide unit with increasing concentration of O atom. The specific physical reason is still unclear to us.…”
mentioning
confidence: 73%
“…31 This method has been verified well to describe the interaction between TM and O in our previous work. 8 [32][33][34][35] Therefore, we believe this method can give a good description of the interaction between TM and O atoms. We considered many possible initial configurations to identify the low-lying and the ground state structure of these TM n O m clusters.…”
Section: Methodsmentioning
confidence: 99%
“…[28] Daneben gibt es mehrere rechnerische Studien zu V 2 O 2 ,d ie alle eine rhombische Struktur aber verschiedene elektronische Zustände vorhersagen. Wang,Gong und Wang [34] bestimmten mit dem PBE-Funktional einen Grundzustand mit Symmetriebruch (DND-Basissatz), lieferten aber keine weiteren Informationen, nicht einmal den V-O-Abstand. Jakubikova, RappØ und Bernstein [33] fanden mit dem BPW91-Funktional und dem LANL2DZ-Basissatz einen 7 A''-Zustand.…”
unclassified
“…For example, small clusters like (ZnO) n , (V 2 O 5 ) n , (CrO 3 ) n form planar structures with very small sizes, and some small clusters present novel magnetic properties 8, [10][11][12] . For scandium (Sc), continuous interests are shown for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxide clusters have attracted enormous attention because their structural, electronic, and magnetic properties are often quite different from those in their bulk phase [1][2][3][4][5][6][7][8][9][10] . For example, small clusters like (ZnO) n , (V 2 O 5 ) n , (CrO 3 ) n form planar structures with very small sizes, and some small clusters present novel magnetic properties 8, [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%